Desempenho de frangos de corte alimentados com DDGS na fase final (35-42 dias) - MAAS, Adriano Rasia; DE SOUZA, Andréia Froés Galuci Oliveira; BRONSTRUP, Lamayson Gabriel Schirmann; DE MEDEIROS, Gabriel Dias; RISSO, Natália Matos; NOGUEIRA, Lavínia Rodrigues (ANAIS DO ENIC, 2025)
-